Pengembangan Modul Pencegahan Kekerasan Dalam Pacaran Pada Siswa SMP - Angelia Margareta Dian Saputri; Setiawan, Antonius Ian Bayu (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
This study aims to develop a dating violence prevention module (KDP) as a medium for guidance and counseling services for junior high school students. The research objectives are: (1) to design and develop a dating violence prevention module tailored to students’ needs; (2) to assess the feasibility of the module based on evaluations by media and material expert validators; (3) to evaluate the module’s feasibility based on user assessments from guidance and counseling teachers; and (4) to determine the module’s effectiveness in enhancing students’ understanding of dating violence prevention. This research adopts a research and development approach using the 4D model (Define, Design, Develop, and Disseminate). Participants include two expert validators, three guidance and counseling teachers, and 71 junior high school students for the limited field trials. Data collection utilized validation questionnaires, teacher assessment scales, and student pretest and posttest instruments. Data were analyzed descriptively to evaluate the module’s feasibility and inferentially, using normality tests and paired sample t-tests, to determine effectiveness. The results indicate that the dating violence prevention module was rated “very feasible” by both media and material experts and received the same rating from guidance and counseling teachers. The effectiveness test revealed normally distributed data and a significant difference between pretest and posttest scores, with a significance value of 0.000 (<0.05). This finding confirms that the module is effective in improving students’ understanding of dating violence and can be utilized as a preventive tool in classical guidance services at schools.